Financial Development, Financial Innovations, and Economic Progress in Nigeria - Michael, Maxwell Ihemeonu; Brůna, Karel, 1973-; Šíma, Ondřej; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This study examines the impact of financial development and innovations on economic growth in Nigeria from 1990 to 2022. The research used the auto-regressive distributed lag (ARDL) model for empirical analysis. The findings reveal that financial institution development has a short-run positive but insignificant impact and a long-run negative significant impact on economic growth in Nigeria. Financial market development has a short-run negative and significant impact, with a long-run positive and insignificant impact on economic growth in Nigeria. Financial innovation has a short-run and long-run positive and significant effect on economic growth in Nigeria, with a higher long-run impact. Inflation, gross fixed capital formation, and trade openness have a short-run positive and significant impact on economic growth in Nigeria. Whereas in the long run, the impact of inflation and trade openness on economic growth is negative and significant, with gross fixed capital formation impacting economic growth positively and insignificantly. Policy recommendations for Nigeria's economic growth include strengthening financial regulations, enhancing institutional capacity, and promoting financial inclusion through initiatives like expanding credit for SMEs and improving financial literacy. To deepen Nigeria's financial markets, policymakers should focus on developing infrastructure, promoting stock exchange listings, and encouraging foreign investment. Supporting fintech and digital payment systems development through digital infrastructure investments, innovation-promoting regulatory frameworks, and private sector partnerships can maximize the positive impact of financial innovation.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses